Comfort and well-being as concepts in use in nursing - de Oliveira, Célia Simão (2013)
This paper presents the author’s perspective on the level of differentiation and use of the concepts ‘comfort’ and ‘well-being’ in the area of health in general, and particularly within the context of nursing. This paper aims to define these concepts and to outline their connection with the practice of nursing and it’s social function. In this context, it equates the advantage and proposes the use of the concept ‘comfort’, with the aim of approximation and conceptual and clinical harmonization; that is to say, it seeks to show, from the concept of “comfort”, its adjustment to what nursing seeks as a result of its social contribution.